Penggunaan Metode Small Group Discussion Untuk Meningkatkan Kemampuan Guru Dalam Menyusun RPP Satu Lembar Di SD Negeri 2 Sembungan Kecamatan Nogosari Semester 2 Tahun Pelajaran 2019/2020 - Sunardi, Sunardi (Jurnal Pendidikan Indonesia, 2022)
Being an educator of course in every process of teaching and learning activities must have a guide called Learning Implementation Plan (RPP). So important is the role of lesson plans for students to help achieve the goals set, so simplifying the lesson plans will be very helpful in increasing the effivtiveness of educator in implementing them. Educational staff need to be empowerd effectively and efficiently to achieve optimal results, but still in a pleasant condition. On of them is through School Action Research (PTS) activities. Changes in the education system based on the results of the School Action Research (PTS) will make it easier for all school members to develop their potential optimally. Therefore, an effective model is needed to stimulate skills. One of them can be with a small group discussion. The purpose of this study was to determine the implementation of guidance to teachers and increase the ability of teachers in preparing a one sheet learning implementation plan (RPP) throuhj the Small Group Discusstion method. The type of research used is school action research (PTS). PTS is a way to improve school management through increasing the professionalism of the principal because the principal is the person who knows best everything that happens in the school. The results showed that the Smaal Group Discussion method was able to create a training atmosphere, increase the active participation of discussion participants (teachers) to exchange experiences and throughs, and effectively improve the ability of discussion participants (teachers) in compiling a one sheet lesson plan (RPP).